Navigating sustainable development: management challenges and solutions in the oil and gas sector - Kudratkhodjaeva , Ziyoda (GREEN ECONOMY AND DEVELOPMENT, 2025)
Governance in the context of natural resources refers to the structures, processes, and institutions through which power is exercised in the allocation and management of resources, as well as in the decision-making processes associated with these activities. It encompasses the interplay of political, economic, and social dynamics, ultimately modeling how resource management benefits both current and future generations. In the oil and gas sector, governance plays a fundamental role not only in enhancing operational efficiency but also in ensuring accountability and transparency in the utilization of these valuable resources. Effective governance mechanisms can mitigate conflicts, combat corruption, and promote fair practices, thereby contributing to a more equitable distribution of the benefits derived from hydrocarbon extraction.